Studi Hubungan Vandalisme dengan Setting Taman Lapangan Puputan Badung I Gusti Ngurah Made Agung Denpasar - Bali - UTAMININGTYAS, ANNISA; ASTININGSIH, A.A.MADE; MAYUN, IDA AYU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol. 1, No. 2, Oktober 2012, 2012)
ABSTRACT Study of Relation of Vandalism with Field Puputan Badung I Gusti Ngurah Made Agung Garden Setting, Denpasar – Bali. Puputan field is one of open green spaces in Denpasar which is visited mostly by local people, with the increase in traffic it would appear some problems, vandalism is one of them. Aims of the study are analyzing relation between environmental factor and setting that affect and studying the planning system and proper management. The analysis method used is explorative descriptive, in which data source was derived from observations, structured interviews (120 respondents), and the literature study. The result show the highest vandalism activity value that is done in this area is do not dispose of waste in place and the highest object subjected to vandalism is shrub. Environmental factor that affects this activity are limited facilities of dump and the existence of previous trash, while the setting that affects are sit on the planter box, volumes of the dump were slightly and not strategic placement. This area needs planning system and management setting appropriate to solve these problems. Keyword : Vandalism, Setting, Garden.
Keywords: Vandalism, Setting, Garden.